Understanding dormancy breakage and germination ecology of Cynara cardunculus (Asteraceae). (15th October 2018) - Huarte, H R; Borlandelli, F; Varisco, D; Batlla, D
Summary: Cynara cardunculus is a troublesome weed in temperate grazing lands. Cynara cardunculus achenes are usually dormant at dispersal and require alternating temperatures to terminate dormancy and germinate. Laboratory and glasshouse experiments were conducted to determine (i) the treatments able to terminate dormancy and (ii) the effect of environmental factors and agronomic practices on germination and emergence of non‐dormant (dry after‐ripened) achenes. Scarification, hydrogen peroxide and sodium hypochlorite promoted germination of dormant achenes. Dry after‐ripening and cold stratification were tested in two different populations. Dormancy of both populations was released from dormancy by dry after‐ripening. In contrast, cold stratification allowed dormancy release in just one of the populations, while the other was induced into secondary dormancy. Germination of non‐dormant (dry after‐ripened) achenes was maximum in a range of temperatures from 10 to 20°C and was inhibited at higher temperatures. Reduction of osmotic potential below −0.6 MPa led to a decrease in final germination. These results explain synchronic emergence of C. cardunculus seedlings in autumn after dormancy release during summer. Maximum seedling emergence was close to 60% at soil depths of 1 cm and only decreased as depth increased over 6 cm. In contrast, seedling emergence was not reduced by the presence of cover residues, while a flooding duration of 21 days was required to suppress emergence significantly. These results suggest that the deep burial of achenes and agronomic practices that take advantage of synchronic emergence of achenes could be useful tools leading to better long‐term management of C. cardunculus .